New records of bat ectoparasites (Diptera, Hemiptera and Siphonaptera) from northern Argentina - Autino,Analía G (2009)
New species of bat-ectoparasite insects are added to the fauna of Argentina and distributional limits are extended for others, based on information obtained from 21 species of bats collected. New data is reported for the distribution of 23 species of bat ectoparasites, of which 17 belong to the Order Diptera [14 Streblidae: Anastrebla caudiferae Wenzel, Anatrichobius scorzai Wenzel, Aspidoptera phyllostomatis (Perty), Megistopoda aranea (Coquillett), M. proxima (Sèguy), Metelasmus pseudopterus Coquillett, Noctiliostrebla aitkeni Wenzel, N. dubia (Rudow), Paradyschiria fusca Speiser, Paradyschiria sp., Strebla chrotopteri Wenzel, Strebla diaemi Wenzel, Trichobius parasiticus Gervais y Xenotrichobius noctilionis Wenzel, and three Nycteribiidae: Basilia carteri Scott, B. plaumanni Scott y B.neamericana Schuurmans Stekhoven (Jr)], three belong to the Order Siphonaptera [one Ischnopsyllidae: Myodopsylla isidori (Weyenbergh), one Tungidae: Rhynchopsyllus pulex Haller, and one Stephanocircidae: Craneopsylla m. minerva (Rothschild)] and three belong to Order Hemiptera [two Polyctenidae: Hesperoctenes fumarius (Westwood) and H. vicinus Jordan, and one Cimicidae: Latrocimex spectans Lent]. Some records are new for Argentina, while others are new for the provinces of Corrientes, Chaco, Entre Ríos, Jujuy, Misiones and Salta. Also new host-parasite relationships are reported.